REPORT ON THE 2022 ONLINE COURSE ON EDUCATION FOR ETHNIC-RACIAL RELATIONS (Citizenship in Action: Extension and Culture Magazine, 2025)
This paper presents an experiential report on the 2022 Online Extension Course on Education for Ethnic-Racial Relations. The course was developed within the scope of UEMG's extension projects at the Carangola campus, reaching students from the local unit, other units, and even other universities. The course aimed to foster an anti-racist awareness among teachers and professionals in training. To achieve this, video conferencing classes were offered, along with study materials in text and video formats, as well as online assessment activities designed to structure learning and collaboration within the class. The course concluded with the creation of lesson plans and anti-racist professional actions, which demonstrated excellent student engagement with the topic. This paper will present the overall structure of the course – its planning, execution, and results – while reflecting on its impact through selected excerpts from students' reflections, highlighting the significant effects that an extension activity can have on the community.
Keywords: Online course; Education; Ethnic-racial relations; Anti-racist awareness; Anti-racist professional actions